Efficient Gating of Ion Transport in Three‐Dimensional Metal–Organic Framework Sub‐Nanochannels with Confined Light‐Responsive Azobenzene Molecules. Issue 31 (25th May 2020) - Qian, Tianyue; Zhang, Huacheng; Li, Xingya; Hou, Jue; Zhao, Chen; Gu, Qinfen; Wang, Huanting
Abstract: 1D nanochannels modified with responsive molecules are fabricated to replicate gating functionalities of biological ion channels, but gating effects are usually weak because small molecular gates cannot efficiently block the large channels in the closed states. Now, 3D metal–organic framework (MOF) sub‐nanochannels (SNCs) confined with azobenzene (AZO) molecules achieve efficient light‐gating functionalities. The 3D MOFSNCs consisting of a MOF UiO66 with ca. 9–12 Å cavities connected by ca. 6 Å triangular windows work as angstrom‐scale ion channels, while confined AZO within the MOF cavities function as light‐driven molecular gates to efficiently regulate the ion flux. The AZO‐MOFSNCs show good cyclic gating performance and high on–off ratios up to 17.8, an order of magnitude higher than ratios observed in conventional 1D AZO‐modified nanochannels (1.3–1.5). This work provides a strategy to develop highly efficient switchable ion channels based on 3D porous MOFs and small responsive molecules. Abstract : Light‐switchable metal–organic framework (MOF) ion channels are constructed by in situ growth of 3D UiO‐66 frameworks with light‐responsive azobenzene (AZO) guests in polymer nanochannels. The confined AZO molecules function as molecular gates to control ion flux through the channels, with an on–off ratio of about 17.8. The gating efficiency is an order of magnitude higher than those of conventional AZO‐modified nanochannels.